Performance measurement and management: a system of systems perspective - Bourne, Mike; Franco-Santos, Monica; Micheli, Pietro; Pavlov, Andrey (Taylor & Francis, 2017)
Despite changes in tools and practices, the conceptual foundations of performance measurement and management (PMM) are still predominantly rooted in control systems research. While PMM approaches have delivered significant organisational benefits, including creating alignment, supporting monitoring and control, and enabling prediction and optimisation of resource allocation, this paper argues that this paradigm is not capable of responding to increasingly complex and highly uncertain organisational environments. Drawing on ideas emerging in the literature on systems engineering and complex systems, we propose a novel perspective that considers PMM from a ‘system of systems’ (SoS) point of view, whose essential characteristics are autonomy, belonging, connectivity, diversity and emergence. After identifying the assumptions underpinning existing PMM approaches, we outline a SoS-based paradigm to PMM and conclude by articulating the main implications for the practice of PMM and setting out a research agenda.
Keywords: Performance management; Performance measures; Performance measurement; Control systems; System of systems